Analysis and Optimization of Horizontal Centrifugal Casting Process for Thick Walled Alloy Layers in Tilting Pad Bearings - Jun, Ye; Jing, Jin; Guobiao, Wang; Zhaohui, Xu; Huangsha, Guo (Manufacturing Technology Journal, 2025)
The optimization of process parameters plays a critical role in controlling temperature and velocity fields during centrifugal casting, which is essential for mitigating shrinkage porosity defects caused by uneven cooling in thick walled bearing alloy layers. In this study, two sequential numerical models were devel-oped using ProCAST software to simulate gravity filling and centrifugal solidification stages. The effects of key parameters, including inlet cross-sectional area and centrifugal rotational speed, on flow field characteristics were systematically analyzed. By using an orthogonal experimental design, we deter-mined the optimal parameters: a melt temperature of 440 °C for the Babbitt alloy, an initial temperature of 280 °C for the bearing blank, a filling inlet diameter of 16 mm, and a rotational speed of 340 r/min. Bearing alloy layers manufactured according to these optimized parameters exhibit no evident shrinkage or cracks on their surfaces. The high quality finished products meet the design requirements, thereby validating the accuracy of the numerical simulation.
Keywords: Centrifugal Casting; ProCAST; Shrinkage Porosity; Orthogonal Experiment